2003
DOI: 10.1128/jcm.41.10.4525-4530.2003
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Acute Diarrhea in Adults in Southwestern Nigeria

Abstract: Stool specimens from 113 adult outpatients with diarrhea in southwestern Nigeria and 63 controls were examined for bacterial and parasitic enteric pathogens. Enterohemorrhagic Escherichia coli (EHEC) (P < 0.02), enteroaggregative E. coli (EAEC) (P < 0.02), and Entamoeba histolytica (P < 0.0002) were significantly associated with diarrhea. Salmonella, Shigella, nontoxigenic Vibrio cholerae, other categories of diarrheagenic E. coli, as well as a variety of helminths were recovered more frequently from the stool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
85
3
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(111 citation statements)
references
References 39 publications
10
85
3
3
Order By: Relevance
“…[14]. EHEC was significantly associated with diarrhea in that study (even with outbreak cases removed) and was the most common bacterial pathogen recovered from bloody diarrhea specimens in which only one pathogen was identified [14].…”
Section: Enterohemorrhagic E Colimentioning
confidence: 99%
See 3 more Smart Citations
“…[14]. EHEC was significantly associated with diarrhea in that study (even with outbreak cases removed) and was the most common bacterial pathogen recovered from bloody diarrhea specimens in which only one pathogen was identified [14].…”
Section: Enterohemorrhagic E Colimentioning
confidence: 99%
“…Over the last decade, EIEC were sought but not found in one Gabonese study and studies from Kenya, Mozambique, Ghana and Nigeria also identified a small number of EIEC isolates but saw no significant association with disease [14,15,20,[134][135][136]. In Senegal, ipaH-positive E. coli (ipaH is a marker for Shigella and EIEC) were recovered from 16 of 279 people with diarrhea and 8 of 276 controls (P < .000001) [137].…”
Section: Enteroinvasive E Coli and Shigellamentioning
confidence: 99%
See 2 more Smart Citations
“…and Shigella spp. are the bacterial agents which are mostly isolated from stool samples of diarrheal patients, especially in rural areas from developing countries 6,7 . Additionally, Clostridium difficile, another bacterial diarrheal agent, is a big threat for children in both community and hospitals 8,9 .…”
Section: Introductionmentioning
confidence: 99%